An observational cross-sectional study on the characteristics of children and adolescents with non-specific spinal pain stratified by pain severity - Brigitte Wirth; Christina Knecht; Mette Hobaek Siegenthaler; Petra Schweinhardt (BMC, 2024)
Abstract Background Distinguishing self-limiting ('trivial') from potentially consequential spinal pain in childhood and adolescence is crucial to prevent over- or under-medicalization. The aim of this study was to stratify participants for severity of spinal pain and to investigate associations of pain severity with potential consequences of pain and some psychophysical and clinical factors. Methods In 2020 and 2021, children and adolescents took part in a voluntary population-based spine screening event across Switzerland organized by the Swiss Chiropractors Association. The screening consisted of a questionnaire (14 questions) based on the Young Spine Questionnaire and a clinical examination by a chiropractor. Three subgroups of pain severity [no pain (including mild, occasional pain), one-sited moderate pain, one-sited severe or moderate/severe pain at multiple sites of the spine] were formed by combining the self-reported measures for pain intensity and pain frequency for two recall periods (lifetime, last week) according to literature. Multivariable logistic regression analyses were conducted to determine the associations between pain severity and potential pain consequences (impact of spinal pain on health and seeking medical advice because of spinal pain), as well as between pain severity and some psychophysical factors (head and/or belly pain, sleep problems, daytime tiredness) and clinical measures [trunk symmetry (rib hump), trunk muscle endurance (plank position)]. Results Of all participants (N = 457; 6-16 years; mean age = 10.9 ± 3.0 years; 220 boys), those with most severe spinal pain and with one-sited moderate pain in the last week had higher odds for reporting an impact of spinal pain on their health (OR = 13.5, 95%CI = 4.9-36.8; OR = 4.7, 95%CI = 1.5-14.4) and for searching medical advice because of spinal pain (OR = 11.6, 95%CI = 4.5-30.1; OR = 3.9, 95%CI = 1.6-9.2). Headache and/or belly pain (OR = 2.6, 95%CI = 1.2-5.5) and daytime tiredness (OR = 3.2, 95%CI = 1.3-7.9) increased the odds for having most severe pain compared to having no pain. The clinical measures were not associated with pain severity. Conclusion Stratification by pain severity, particularly when asked for pain in the last week, might help to minimize over- and under-medicalization of spinal pain in childhood and adolescence. Prospective studies are needed to clarify the relevance of the investigated clinical tests in the context of adolescent spinal pain.